Imbalanced T-Cell Subsets May Facilitate the Occurrence of Osteonecrosis of the Femoral Head - Chen C; Zhao X; Luo Y; Li B; Li Q; Zhao C; Huang Y; Kang P (Dove Medical Press, 2022)
Changjun Chen,1 Xin Zhao,1,2 Yue Luo,1 Bohua Li,1 Qianhao Li,1 Chengcheng Zhao,1 Yan Huang,3 Pengde Kang1 1Department of Orthopedics, West China Hospital, Sichuan University, Chengdu, People's Republic of China; 2Department of Orthopedics, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, People's Republic of China; 3Health Management Center, West China Hospital, Sichuan University, Chengdu, People's Republic of ChinaCorrespondence: Yan Huang, Health Management Center, West China Hospital, Sichuan University, Chengdu, People's Republic of China, Email huangyan_0819@163.com Pengde Kang, Department of Orthopedics, West China Hospital, Sichuan University, Chengdu, People's Republic of China, Email kangpengde1969@163.comBackground: Osteonecrosis of the femoral head (ONFH) is a complex disease resulting in degeneration of the hip joint. The pathogenesis of ONFH is largely unknown, but alterations in immunological factors have been proposed to play a role.Methods: We included 109 patients with ONFH and 109 age-, sex-, and body mass index-matched healthy controls in this study. The percentage of circulating CD3+, CD4+, and CD8+ lymphocytes among the total lymphocytes was identified by flow cytometry and compared between the cases and controls. Subgroup analysis within each etiological group and correlation analysis of T-cell subset levels with disease duration were performed. Furthermore, we compared the expression patterns of CD4, RANKL, and FoxP3 in the femoral head of healthy and glucocorticoid (GC)-treated ONFH rats.Results: The results showed that CD3+ and CD4+ T-cell counts and the CD4+/CD8+ ratio were significantly higher in patients with ONFH and that CD3+ lymphocyte levels were negatively correlated with disease duration. The CD4+ T-cell levels and CD4+/CD8+ ratios in the GC-ONFH etiological group were lower than those in the idiopathic-, traumatic-, and alcoholic-ONFH groups, while the CD8+ T-cell levels were higher. Furthermore, the CD3+, CD4+, and CD8+ T-cell counts and the CD4+/CD8+ ratio were higher in the GC-ONFH group than in the control group. Finally, we observed diminished levels of FoxP3/CD4 double-positive T regulatory cells and increased RANKL+ T-cell levels in the bone marrow of the femoral head in GC-ONFH rats.Conclusion: The imbalance of T-cell subsets might be involved in the pathophysiological process of ONFH, and diminished CD4+/FoxP3+ T regulatory cells may be associated with increased RANKL+ T cells in the bone marrow of the femoral head in GC-ONFH, which may facilitate bone resorption and collapse of the femoral head.Trial Registration: This study was registered in the Chinese Clinical Trial Registry (Registration number: ChiCTR2100042642).Keywords: CD3+, CD4+, lymphocytes, ONFH, osteoimmunology